Competence-based education and the limitations of critique. (1st September 2016) - Edwards, Richard
Abstract: Drawing upon the work of Foucault and Latour, this article reflects on 25 years of critique of competence-based education and its continuing strength as a way of framing education and training. Using an example from England, it rehearses the argument from Foucault that, despite its student-centred discourse, competence-based education can be positioned as one of the disciplining techniques in modern societies. However, beyond the research community, such critiques have had little impact. The article seeks to explore this by drawing upon Latour's argument that conventional forms of critique have run out of steam. This indicates the need for new forms of educational critique as a means of having impact on policy and practice. The article is theoretically driven and exploratory.